x`sqrt(1+y^2)dx-ysqrt(1+x^2)dy=0` solve using variable separable.
- print Print
- list Cite
Expert Answers
sciencesolve
| Certified Educator
calendarEducator since 2011
write5,349 answers
starTop subjects are Math, Science, and Business
You need to start separate the variables, hence, you need to move the negative member to the right side, such that:
`xsqrt(1 + y^2)dx = ysqrt(1+x^2)dy`
You need to divide by `sqrt(1 + y^2)` both sides, such that:
`xdx = (ysqrt(1+x^2)dy)/(sqrt(1 + y^2))`
You need to divide by `sqrt(1 + x^2)` both sides, such that:
`(xdx)/(sqrt(1 + x^2)) =...
(The entire section contains 175 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- Given z = ln(sqrt x^2 + y^2), show that x dz/dx + y dz/dy = 1Calculus of several variables...
- 1 Educator Answer
- How to solve the following differential equation. y''-3y^2 = 0, y(0)=2, y'(0)=4 Use the...
- 1 Educator Answer
- Find dy/dx by implicit differentiation: tan(x-y) = y/(2+x^2)
- 1 Educator Answer
- Find the domain and range of the following: y = x^2 , y = sqrt(1 – x^2), y = 1/x, y = sqrt(x) ,...
- 2 Educator Answers
- #2 What is dy/dx if y = log(x+1/x).
- 2 Educator Answers